All Citizens of Christ: A Cosmopolitan Reading of Unity and Diversity in Paul's Letters - Park, Jeehei, (Biblical Interpretation Series ;, 2022)
This work is both a critical response to the abuse and misuse of Paul's words on unity and a proposal to read them as a way to care about "others."